2016
DOI: 10.1016/j.jss.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

An automatic process for weaving functional quality attributes using a software product line approach

Abstract: Some quality attributes can be modelled using software components, and are normally known as Functional Quality Attributes (FQAs). Applications may require different FQAs, and each FQA (e.g., security) can be composed of many concerns (e.g., access control or authentication). They normally have dependencies between them and crosscut the system architecture. The goal of the work presented here is to provide the means for software architects to focus only on application functionality, without having to worry abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 31 publications
0
36
0
2
Order By: Relevance
“…Degree of automation and effort. The degree of automation is a measure that compares the software elements (e.g., number of components, lines of code) that are manually defined with those that are automatically generated [22]. This metric allows discussing about the development effort, degree of reuse and productivity of applying a specific approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degree of automation and effort. The degree of automation is a measure that compares the software elements (e.g., number of components, lines of code) that are manually defined with those that are automatically generated [22]. This metric allows discussing about the development effort, degree of reuse and productivity of applying a specific approach.…”
Section: Discussionmentioning
confidence: 99%
“…The annotative variation point associated with this feature includes a reference to the component affected by the annotation. When the ImageFromURL feature is selected in a configuration, the derivation engine will resolve the annotation with the semantic specified and will generate the final product's code with the variability resolved and without any annotations left (in 3 (a) lines 5, 9-14 are removed and also in (b) comments of line 9, 13, 17 and lines [19][20][21][22][23]. The HTML and Javascript code show respectively one variant of the view and the controller implementations of the PostEditor component (implemented using the MVC pattern).…”
Section: Applying Our Approach To the Blog Splmentioning
confidence: 99%
“…Specifically, each variation point (dashed line) defines a transformation (eg, object existence, object substitution, and parameter assignment) in the software architecture that will be executed by the CVL engine when a particular configuration is selected in the variability model, adapting the components of the autonomous vehicle. () For example, when the context changes because the vehicle joins a motorway, a new configuration is generated: The new context is selected in the tree, and the IDM model is automatically selected in the configuration due to the cross‐tree constraints defined in OCL. The CVL engine will resolve the variability, changing the IDM component to be the car‐following model in the autonomous vehicle.…”
Section: Reconfigurable Vehicle Controller Agentmentioning
confidence: 99%
“…4 The bottom half of Figure 1 defines a transformation (eg, object existence, object substitution, and parameter assignment) in the software architecture that will be executed by the CVL engine 37 when a particular configuration is selected in the variability model, adapting the components of the autonomous vehicle. 38,39 For example, when the context changes because the vehicle joins a motorway, a new configuration is generated: The new context is selected in the tree, Each configuration of the controller is a set of choices in the variability model (features in grey in Figure 1). In our approach, we first generate a particular configuration of the reconfigurable vehicle controller agent, which is able to detect changes in weather conditions (rain intensity) and evaluate the traffic quality based on the selected indicators of safety (time to collision, post-encroachment time) and efficiency (travel time).…”
Section: Variability Modelling Of the Autonomous Vehicle: Traffic Conmentioning
confidence: 99%
“…A first step toward mitigating this problem is applying the separation of concerns principle to model the variability of security from the early stages of the software's development. Thus, security concerns are modeled separately from the base applications and later customized to the application's requirements and composed at particular points of the application model [4,5]. It has been demonstrated that this approach has many advantages [4][5][6], such as high reusability, low coupled components and high cohesive software architectures.…”
Section: Introductionmentioning
confidence: 99%